Pengaruh Risiko Kredit, Kecukupan Modal, dan Likuiditas Terhadap Profitabilitas Perbankan - Cindy Cindy; Hartono Hartono (Journal of Business and Economics Research (JBE), 2026)
The The objective of this study is to analyze the impact of credit risk, capital adequacy, and liquidity on the profitability of banks listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. A quantitative approach was applied in this study using secondary data (annual financial reports). Data analysis was conducted using panel data regression techniques with the assistance of the EViews 13 program. The total population comprised 48 banks, with 43 banks selected using purposive sampling. The findings of this study indicate that credit risk (NPL) has a positive and significant effect on profitability with a coefficient of 0.080181 and a significance level of 0.0063, capital adequacy (CAR) has a positive and significant effect with a coefficient of 0.016051 and a significance value of 0.0412, and liquidity (LDR) has a positive and significant effect with a coefficient of 0.006350 and a significance value of 0.0490. The adjusted R-squared value of 5.64% indicates that these three variabels collectively explain the variation in profitability, while the remaining 94.36% is influenced by other factors outside the model. The research findings suggest that controlled credit risk management, adequate capital adequacy, and effective liquidity management can support improvements in bank profitability. This study provides empirical evidence regarding the importance of managing internal banking factors in maintaining financial performance during the post-pandemic economic recovery period. The findings are expected to serve as a basis for bank management and investors in making decisions related to banking performance and stability.